Effect of Combinative Pretreatments on Cellulose-to-Glucose Conversion of Empty Palm Fruit Bunch (EFB) - Timilsena, Yakindra Prasad; Brosse, Nicolas (Journal of Food Science and Technology Nepal, 2014)
Various methods of pretreatments were investigated to their effect on cellulose to glucose conversion efficiency on enzymatic hydrolysis of a tropical agro-industrial waste residue (empty palm fruit bunch, EFB). Four different kinds of combinative pretreatments (autohydrolysis with and without naphthol, dilute acid prehydrolysis, soda prehydrolysis and enzymatic prehydrolysis) were tested for delignification during the first and the second steps of pretreatment. Each prehydrolysis step was seconded by the organosolv delignification with the same conditions of pretreatment. It was observed that all the combinative methods were far more efficient in delignification and enzymatic hydrolysis ability as compared to its one step counter parts. The combinative pretreatment method involving dilute acid prehydrolysis followed by organosolv delignification revealed the best result with respect to lignin removal and enzymatic hydrolysis. The resultant pulp contained very low Klason lignin ( 5%) with high sugar conversion ratio (64% total reducing sugars). DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10613 J. Food Sci. Technol. Nepal, Vol. 7 (81-85), 2012